EFEKTIVITAS ORGANISASI PEMERINTAH KECAMATAN WANEA KOTA MANADO - TOAD, VICKY SWITLY; RARES, JOYCE; POMBENGI, JERICHO (Sam Ratulangi University, 2018)
Abstract: Aim Research is for knowing effectiveness organization government districts wanea city manado.Research this use method approach descriptive quantitative. Effectiveness organization government districtswanea seen from five dimensions effectiveness organization ie production, efficiency, clerk of employeeadaptation or flexibility, and development. Informant research as many as six people that is camat wanea,secretary districts, head sexy system government, head sexy service general, a lurah. Collection data useguidelines interview, while technique analysis that used is analysis model interactive from Miles andHubernann.Based on results analysis data withdrawn conclusion that effectiveness organization government districtswanea seen from dimensions production, efficiency, satisfaction employees, adaptation or flexibility, anddevelopment, all not yet maximum however already enough good.Based on results research could recommended suggestion : (1) Improve quantity and quality program/activitiesand implementation; (2) Utilize on right and optimal potency human resources employees, budget/fund, andmeans work; (3) Improve appreciation to employees and his welfare; (4) Improve power responsive to everydevelopment external and internal; and (5) continue attempted fix performance.Keywords : Effectiveness organization, government districts.